A systematic literature review of narrative analysis in recent translation studies - Wang, Li; Ang, Lay Hoon; Abdul Halim, Hazlina (Universiti Putra Malaysia Press, 2020)
As early as the 1980s, the narrative has been redefined by sociologists and communication theorists as a way to constitute social identity; however, to date, it has not been specified how far narrative analysis has reached into translation studies because of the different understandings of the term. Therefore, it is essential for researchers to carry out a literature review of narrative analysis in this field in a more complete way. This study reviews the body of literature that uses narrative analysis in recent translation studies. The method used in this study is a systematic literature review, which involves pre-set criteria in selecting academic articles to be surveyed within a five-year period (1 January 2014 to 31 December 2018) and a qualitative synthesis of the findings. Through description and analysis of the titles, abstracts, keywords, and full papers (when necessary) of the selected 92 academic articles, based on a revised PRISMA flow, this study arrives at a holistic and systematic assessment of this approach over the past five years to guide future research in translation studies. The main findings reveal that narrative analysis has not yet become a mainstream approach in translation studies. The focus of studies in this field should be shifted from empirical research in how narrative analysis is used as a tool towards theoretical reflection on what narratives are. What is more, new fields still await examination concerning research methods and subjects.